Investigating the relationship between reading skills of students with autism spectrum disorder and solving mathematical word problems - Maryam Shahmohammadi; Elahe Aminifar; Maryam Mavisat (Iranian Journal of Educational Research)
Objective: Reading proficiency and problem-solving capabilities represent two distinct yet significant cognitive faculties that exert a considerable influence on both personal and societal dimensions of individuals' lives. Problem-solving constitutes a fundamental component of cognitive processing. In the absence of an accurate delineation and comprehension of the problem, selecting an appropriate method for its resolution becomes untenable. A critical competency requisite for the accurate interpretation of the problem is reading proficiency. This study aims to examine the correlation between the reading capabilities of students diagnosed with autism spectrum disorder and their aptitude for solving mathematical verbal problems. Methods: The methodology employed in this research is descriptive (non-experimental) quantitative and correlational in nature. The statistical population comprises high-functioning autism students (level one) attending both regular and specialized educational institutions within Khuzestan province. Data acquisition was facilitated through the use of a standardized reading skills questionnaire alongside a researcher-developed questionnaire focused on verbal and mathematical problems. The analytical approach adopted involved regression analysis and hierarchical methods. Results: The results indicated a significant correlation between the reading proficiency of students with autism spectrum disorder and each of its respective dimensions with the ability to solve mathematical verbal problems. Conclusions: Furthermore, enhancing each of these competencies is likely to concurrently bolster the verbal problem-solving capabilities of students with autism spectrum disorder.